A középfokú oktatás eredményességének területi különbségei a Dél-Alföldön, különös tekintettel a határ menti térségre - Győri, Ferenc (Közép-Európai Közlemények, 2009)
There are serious disadvantages of students in the border zone of the Southern Great Plains Region for becoming outstanding achievers at school. Differences reflect the disparities concerning the opportunities for talent improvement. As it is attested by experience, school achievements are significant indicators of the individuals’ future career. On the other hand, talent improvement within the walls of a school is only one aspect of the many, which hints at the learners’skills and abilities, necessary from the point of view of further and more advanced studies. But several other aspects of secondary school education remain hidden behind the statistics, although, they might also play a role in assisting talented students. Growing inequality in the educational system serves as a warning sign, since it is a well known fact that in modern IT societies and economies the competitiveness of the human resources has become a factor of utmost importance.